Characterization of heat-polymerized monomer formulations for dental infiltrated ceramic networks - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Applied Sciences, 2021)
(1) Objectives: This work examined properties of dental monomer formulations of an aromatic dimethacylate (BisGMA), aliphatic urethane dimethacrylate (UDMA), and triethylene glycol dimethacrylate (TEGDMA). The monomers were combined in different ratio formulations and heat-polymerized containing the initiator benzoyl peroxide (BPO) specifically for the purpose of infil-tration into polymer-infiltrated composite structures. (2) Methods: The monomers were combined in different weight ratios and underwent rheological analysis (viscosity and temperature dependence), degree of conversion, and mechanical properties (elastic modulus, hardness, fracture toughness). (3) Results: Rheological properties showed Newtonian behavior for monomers with a large dependence on temperature. The addition of BPO allowed for gelation in the range of 72.0–75.9◦ C. Degree of conversion was found between 74% and 87% DC, unaffected by an increase of TEGDMA (up to 70 wt%). Elastic modulus, hardness, and fracture toughness were inversely proportional to an increase in TEGDMA. Elastic modulus and hardness were found slightly increased for UDMA versus BisGMA formulations, while fracture toughness ranged between 0.26 and 0.93 MPa.m0.5 for UDMA-and 0.18 and 0.68 MPa.m0.5 for BisGMA-based formulations. (4) Significance: Heat-polymerization allows for greater range of monomer formulations based on viscosity and degree of conversion when selecting for infiltrated composite structures. Therefore, selection should be based on mechanical properties. The measured data for fracture toughness combined with the reduced viscosity at higher UDMA:TEGDMA ratios favor such formulations over BisGMA:TEGDMA mixtures.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Heat polymerization; Mechanical properties; Methacrylate monomer; Resin infiltration